MORPHOMETRIC CHANGES OF CHILDREN WITH SCOLIOSIS - Kamalova Shakhnoza Muzaffarovna (Ethiopian International Journal of Multidisciplinary Research, 2025)
The study studied the morphometric changes in body parts of 20 boys and 30 girls 8 years old with scoliosis (n=50) and compared with healthy children (n=50, 20 boys and 30 girls). It was established that scoliosis leads to violations of not only the functions of the musculoskeletal system, but also the development of negative shifts in anthropometric parameters.